Chitosan and its derivatives as polymeric anti-viral therapeutics and potential anti-SARS-CoV-2 nanomedicine. (15th August 2022) - Tan, Rebecca Shu Ling; Hassandarvish, Pouya; Chee, Chin Fei; Chan, Lai Wah; Wong, Tin Wui
Abstract: The coronavirus pandemic, COVID-19 has a global impact on the lives and livelihoods of people. It is characterized by a widespread infection by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), where infected patients may develop serious medical complications or even face death. Development of therapeutic is essential to reduce the morbidity and mortality of infected patients. Chitosan is a versatile biomaterial in nanomedicine and exhibits anti-microbial, anti-cancer and immunomodulatory properties. This review highlights the progress in chitosan design and application pertaining to the anti-viral effects of chitosan and chitosan derivatives (hydroxypropyl trimethylammonium, sulfate, carboxymethyl, bromine, sialylglycopolymer, peptide and phosphonium conjugates) as a function of molecular weight, degree of deacetylation, type of substituents and their degree and site of substitution. The physicochemical attributes of these polymeric therapeutics are identified against the possibility of processing them into nanomedicine which can confer a higher level of anti-viral efficacy. The designs of chitosan for the purpose of targeting SARS-CoV-2, as well as the ever-evolving strains of viruses with a broad spectrum anti-viral activity to meet pandemic preparedness at the early stages of outbreak are discussed. Graphical abstract: Unlabelled Image